Evaluation of Commercial Disinfectants Against Bacterial Pathogens Isolated from Broiler Farms - Soliman, Essam S.; Sobeih, Mohamed A.A.; Ahmad, Z. H.; Hussein, M.M.; Moneim, H.A.A. (International Journal of Poultry Science, 2009)
Five disinfectants [TH4® (combination of quaternary ammonium compounds and gluteraldhyde), Microzal® (combination of quaternary ammonium compounds and gluteraldhyde), Incospect IC 22XA (combination of quaternary ammonium compounds, gluteraldhyde and formalin), Povidone Iodine® (iodophore) and Formalin® (commercial formaldehyde 37%) were tested in a laboratory trials against four bacterial isolates (Staphylococcus aureus, Escherchia coli, Klebsiella oxytoca and Pseudomonas aureuginosa) at concentration of (~105) isolated during epidemiological surveillance. The trials were carried in the presence and absence of organic matter (dried yeast 5%) using MIC use-dilution test. Minutely samples were collected for the bacterial counts. In the absence of organic matter, TH4® achieved the 100% killing efficacy against Staphylococcus aureus, Escherchia coli, Klebsiella oxytoca and Pseudomonas aureuginosa after 5, 5, 10 and 5 min (p